Marketing as it relates to special diets - Townsend, Carena Ashley (2017)
The aim of this thesis is to analyze how marketing communications strategies influence consumers to purchase gluten-free products in the United States and the United Kingdom. This thesis is divided into four chapters. The first chapter focuses on the theory of the marketing mix and marketing communication concepts related to the gluten-free food industry. The second chapter focuses on the history of gluten in food production, the rise and expansion of the gluten-free industry and economic impacts. The third chapter compares the marketing strategies of the Barilla Group by comparing their gluten-free pasta and gluten counterpart in the United States and the United Kingdom markets. The last chapter summarizes the research conducted by the author to understand what are the different influences that impact consumers to purchase Barilla products in both markets.